Temporal evolution of polycyclic aromatic hydrocarbons in sediments of the Hooghly river, West Bengal, India - M. Toscanesi; M. Arienzo; L. Ferrara; P. Mondal; M. P. Jonathan; S. K. Sarkar; C. Donadio; M. Trifuoggi (International Journal of Environmental Science and Technology, 2026)
The study evaluated the effect of monsoons on the levels of polycyclic aromatic hydrocarbons in the Hooghly River estuary sediments over 2018–2021. It was observed a cyclical enrichment of organic material, carbonate deposits, and clay over the post-monsoon and impoverishment over the monsoon because of the heavy rains and flood events. The mean total level of polycyclic aromatic hydrocarbons was 1682 ng/g with a wide range of variability depending on the season, 125–6518 ng/g, higher than previous assays and lower than a contemporary survey. Also, there was a marked predominance of the polycyclic aromatic hydrocarbon heavy pool, ~ 83%, with fluoranthene and pyrene making more than 40% of the total hydrocarbons loads and with a large variability of the composition with the monsoon. Concerning the numerical sediment quality guidelines, the mean individual compound levels, and ∑PAHs, do not surpass effect range low, effect range median, and apparent effects threshold limits and keep fairly below thresholds with no evidence of detrimental biological consequences. Temporal trends of polycyclic aromatic hydrocarbons split over two periods after the 2019 monsoon, with a sudden drop in hydrocarbon levels from two times for naphthalene, acenaphthylene, pyrene, benzo(a)anthracene, chrysene, to 6–7 times for phenanthrene, benzo(b)fluoranthene, benzo(a)pyrene, and indeno[1,2,3-cd]pyrene, with an overall decrease of ∑PAHs of threefold from 2948 to 959 ng/g. Monsoon seems to play as a sort of natural attenuation effect, slowing down river decline.

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

MICROorganisms under simulated ICY moon environments: supporting solar system exploration (MICRO ICY project) - C. Pacelli; A. Cassaro; L. Cocola; A. Cordone; M. Del Bianco; M. Esposito; F. Ferranti; M. Ferrara; D. Giovannelli; L. Manfrin; L. Parca; L. Poletto; et al. (Planetary and Space Science, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

A Self-supervised Deep Learning Model for Diagonal Sulcus Detection with Limited Labeled Data - Delfina Braggio; Hernán C. Külsgaard; Mariana Vallejo-Azar; Mariana Bendersky; Paula González; Lucía Alba-Ferrara; José Ignacio Orlando; Ignacio Larrabide (Neuroinformatics, 2024)

Global quantification and distribution of antibiotic resistance genes in oceans and seas: Anthropogenic impacts and regional variability - G. Bonanno Ferraro; D. Brandtner; A. Franco; M. Iaconelli; P. Mancini; C. Veneri; R. Briancesco; A.M. Coccia; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; et al. (Science of The Total Environment, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Tracing the footprints of SARS-CoV-2 in oceanic waters - Giuseppina La Rosa; P. Mancini; M. Iaconelli; C. Veneri; G. Bonanno Ferraro; C. Del Giudice; E. Suffredini; A. Muratore; F. Ferrara; L. Lucentini; M. Martuzzi; A. Piccioli (Science of The Total Environment, 2024)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Liposaccharide-induced sustained mild inflammation fragments social behavior and alters basolateral amygdala activity - Maxine K. Loh; Courtney Stickling; Sean Schrank; Madison Hanshaw; Alexandra C. Ritger; Naijila Dilosa; Joshua Finlay; Nicole C. Ferrara; J. Amiel Rosenkranz (Psychopharmacology, 2023)

Interactions of a boron-containing levodopa derivative on D2 dopamine receptor and its effects in a Parkinson disease model - Antonio Abad-García; A. Lilia Ocampo-Néstor; Bhaskar C. Das; Eunice D. Farfán-García; Martiniano Bello; José G. Trujillo-Ferrara; Marvin A. Soriano-Ursúa (JBIC Journal of Biological Inorganic Chemistry, 2022)

UPLC–QTOF–MS analysis of cytotoxic and antibacterial extracts of Hechtia glomerata Zucc - Tommaso Stefani; Pilar Del C. Morales-San Claudio; María Yolanda Rios; A. Berenice Aguilar-Guadarrama; Leticia González-Maya; Jessica Nayelli Sánchez-Carranza; Maurcio González-Ferrara; María del Rayo Camacho-Corona (Natural Product Research, 2022)

Dredging Impacts on Soil Properties of the Kankakee River System 150 Years after Perturbation - Jack V. Ferrara; Joshua J. Puhlick; Tamatha A. Patterson; Katherine C. Glover (Wetlands, 2020)

A global dataset and model of earthquake-induced landslide fatalities - M. Anna Nowicki Jessee; M. W. Hamburger; M. R. Ferrara; A. McLean; C. FitzGerald (Landslides, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Estimating late spring frost-induced growth anomalies in European beech forests in Italy - M. Bascietto; S. Bajocco; C. Ferrara; A. Alivernini; E. Santangelo (International Journal of Biometeorology, 2019)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Remote sensing in environmental police investigations: aerial platforms and an innovative application of thermography to detect several illegal activities - M. Lega; C. Ferrara; G. Persechino; P. Bishop (Environmental Monitoring and Assessment, 2014)

Source apportion of atmospheric particulate matter: a joint Eulerian/Lagrangian approach - A. Riccio; E. Chianese; G. Agrillo; C. Esposito; L. Ferrara; G. Tirimberio (Environmental Science and Pollution Research, 2014)

Relationships between coastal sand dune properties and plant community distribution: The case of Is Arenas (Sardinia) - G. Fenu; D. Cogoni; C. Ferrara; M. S. Pinna; G. Bacchetta (Plant Biosystems, 2012)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Mercury Levels in Muscle of Six Species of Turtles Eaten by People Along the Rio Negro of the Amazon Basin - Larissa Schneider; Lauren Belger; Joanna Burger; Richard C. Vogt; Camila R. Ferrara (Archives of Environmental Contamination and Toxicology, 2010)

The role of receptivity in the courtship behavior of Podocnemis erythrocephala in captivity - Camila Rudge Ferrara; Larissa Schneider; Richard C. Vogt; Joanna Burger (acta ethologica, 2009)

Computational and experimental evaluation of ornithine derivatives as ornithine decarboxylase inhibitors - J. Correa-Basurto; L. Rodríguez-Páez; E. S. Aguiar-Moreno; P. López-Sánchez; L. M. Espinoza-Fonseca; C. Wong; J. Trujillo-Ferrara (Medicinal Chemistry Research, 2009)

Performance stability of maize genotypes across diverse hill environments in Nepal - D. Sharma; R. C. Sharma; R. Dhakal; N. B. Dhami; D. B. Gurung; R. B. Katuwal; K. B. Koirala; R. C. Prasad; S. N. Sah; S. R. Upadhyay; T. P. Tiwari; G. Ortiz-Ferrara (Euphytica, 2008)

Wheat genetic resources enhancement by the International Maize and Wheat Improvement Center (CIMMYT) - Rodomiro Ortiz; Hans-Joachim Braun; José Crossa; Jonathan H. Crouch; Guy Davenport; John Dixon; Susanne Dreisigacker; Etienne Duveiller; Zhonghu He; Julio Huerta; Arun K. Joshi; Masahiro Kishii; et al. (Genetic Resources and Crop Evolution, 2008)

Wheat grain yield and stability assessed through regional trials in the Eastern Gangetic Plains of South Asia - Ram C. Sharma; G. Ortiz-Ferrara; J. Crossa; M. R. Bhatta; M. A. Sufian; J. Shoran; A. K. Joshi; R. Chand; Gyanendra Singh; R. Ortiz (Euphytica, 2007)

Partnering with farmers to accelerate adoption of new technologies in South Asia to improve wheat productivity - G. Ortiz-Ferrara; A. K. Joshi; R. Chand; M. R. Bhatta; A. Mudwari; D. B. Thapa; M. A. Sufian; T. P. Saikia; R. Chatrath; J. R. Witcombe; D. S. Virk; R. C. Sharma (Euphytica, 2007)

Chemical and Ecotoxicological Characterization of Averno Lake - C. Improta; S. Andini; L. Ferrara (Bulletin of Environmental Contamination and Toxicology, 2004)

Evaluation of the Synthetic Major Component of the Sex Pheromone of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Fernando A. A. Ferrara; Evaldo F. Vilela; Gulab N. Jham; Álvaro E. Eiras; Marcelo C. Picanço; Athula B. Attygalle; Ales Svatos; Rosa T. S. Frighetto; Jerrold Meinwald (Journal of Chemical Ecology, 2001)

Magnetic transcranial stimulation at intensities below active motor threshold activates intracortical inhibitory circuits - V. Di Lazzaro; D. Restuccia; A. Oliviero; P. Profice; L. Ferrara; A. Insola; P. Mazzone; P. Tonali; J. C. Rothwell (Experimental Brain Research, 1998)

Effect of different combinations of sparfloxacin, oxacillin, and fosfomycin against methicillin-resistant staphylococci - A. Ferrara; C. Dos Santos; M. Cimbro; G. Gialdroni Grassi (European Journal of Clinical Microbiology & Infectious Diseases, 1997)